Novel acyl carbamates and acyl / diacyl ureas show in vitro efficacy against Toxoplasma gondii and Cryptosporidium parvum. (December 2020) - Li, Kun; Grooms, Gregory M.; Khan, Shahbaz M.; Hernandez, Anolan Garcia; Witola, William H.; Stec, Jozef
Abstract: Toxoplasma gondii and Cryptosporidium parvum are protozoan parasites that are highly prevalent and opportunistically infect humans worldwide, but for which completely effective and safe medications are lacking. Herein, we synthesized a series of novel small molecules bearing the diacyl urea scaffold and related structures, and screened them for in vitro cytotoxicity and antiparasitic activity against T. gondii and C. parvum . We identified one compound (GMG-1-09), and four compounds (JS-1-09, JS-2-20, JS-2-35 and JS-2-49) with efficacy against C. parvum and T. gondii, respectively, at low micromolar concentrations and showed appreciable selectivity in human host cells. Among the four compounds with efficacy against T. gondii, JS-1-09 representing the diacyl urea scaffold was the most effective, with an anti- Toxoplasma IC50 concentration (1.21 μM) that was nearly 53-fold lower than its cytotoxicity IC50 concentration, indicating that this compound has a good selectivity index. The other three compounds (JS-2-20, JS-2-35 and JS-2-49) were structurally more divergent from JS-1-09 as they represent the acyl urea and acyl carbamate scaffold. This appeared to correlate with their anti- Toxoplasma activity, suggesting that these compounds' potency can likely be enhanced by selective structural modifications. One compound, GMG-1-09 representing acyl carbamate scaffold, depicted in vitro efficacy against C. parvum with an IC50 concentration (32.24 μM) that was 14-fold lower than its cytotoxicity IC50 concentration in a human intestinal cell line. Together, our studies unveil a series of novel synthetic acyl/diacyl urea and acyl carbamate scaffold-based small molecule compounds with micromolar activity against T. gondii and C. parvum that can be explored further for the development of the much-needed novel anti-protozoal drugs. Graphical abstract: Image 1 Highlights: A focused library of acyl/diacyl ureas and acyl carbamates was efficiently prepared. Select compounds inhibited the in vitro growth of T. gondii and C. parvum parasites. The diacyl urea compound JS-1-09 showed good activity against T. gondii parasites. The identified hit shows potential for further development as novel antiprotozoal agent.